Analysis of Twisted tall Structure Considering Lateral Load Using ETABS - A REVIEW - Anmol Khare; Vijay Tembhere; Lokesh Harinkhede (International Journal of Scientific Research in Civil Engineering, 2022)
This examination presents the underlying way of behaving of RCC wound building exposed to dynamic burdens. The similar concentrate between RCC wound building is made. In a wound tall structure different pace of contort for RCC bent building was investigated. The different pace of bend as 10, 12.5 and 15 degrees at the focal point of the RCC wound building was thought of. The demonstrating and investigation is finished utilizing ETABS. Dead loads, live burden, seismic burden and wind loads are allocated for demonstrated designs and results acquired are plotted for boundaries, for example, removal, story float, time-frame and base shear. This paper presents literature review related to analysis of tall structures.